Large Option Trades, Market Makers, and Limit Orders - Berkman, Henk (Review of Financial Studies, 1996)
This article focuses on the difference between market makers and limit orders in their role as suppliers of liquidity. For both sources of liquidity I analyze the price behavior of stocks and options around large option trades and I estimate the premium paid by the initiator of the large trade. My findings suggest that limit orders for options are "picked off" after adverse changes in the underlying stock price. Furthermore, I find that for these transactions there is a permanent change in quotations in the direction of the transaction. After transactions where market makers supply liquidity, quotes tend to return to their pretrade level.